2016
DOI: 10.4103/1596-3519.188892
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of congenital anomalies of the central nervous system in children in Enugu, Nigeria: A retrospective study

Abstract: Background:Congenital anomalies, including those of the central nervous system (CNS), are among the leading causes of morbidity, mortality, and fetal loss.Objective:To determine the prevalence and associated factors of CNS congenital anomalies in children.Methods:A cross-sectional retrospective study of children managed with CNS anomalies was undertaken. Relevant clinical data of identified cases based on standard case definitions were retrieved from their case record files. Data were analyzed using SPSS 20.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
9
25
1
Order By: Relevance
“…(34) The central nervous system is the most frequently affected biological system, followed by the digestive and musculoskeletal systems. These findings agree with that of Eke et al (35) on the epidemiology of congenital anomalies in Nigeria. The highest prevalence of anomalies related to the musculoskeletal system relates to a study from Saudi Arabia, (36) and the genitourinary system finds agreement in a study conducted in Taiwan.…”
Section: Discussionsupporting
confidence: 94%
“…(34) The central nervous system is the most frequently affected biological system, followed by the digestive and musculoskeletal systems. These findings agree with that of Eke et al (35) on the epidemiology of congenital anomalies in Nigeria. The highest prevalence of anomalies related to the musculoskeletal system relates to a study from Saudi Arabia, (36) and the genitourinary system finds agreement in a study conducted in Taiwan.…”
Section: Discussionsupporting
confidence: 94%
“…This is also similar to a cross-sectional retrospective study performed in Enugu, Nigeria which revealed increased incidence of central nervous system anomalies in mothers >35 years of age. 6 There was a statistically significant relationship between knowledge of congenital hydrocephalus and respondents' knowledge of the risk factors of congenital hydrocephalus. The reason for the relatively good knowledge about the risk factors of congenital hydrocephalus was due to attendance of antenatal clinics by the women and health education by the doctors, nurses, and other health workers (80.2%), also most of the respondents who had good knowledge had tertiary level of education (64.7%).…”
Section: Discussionmentioning
confidence: 89%
“…6 No definite relationship of congenital hydrocephalus with maternal age has been reported by most researchers except a cross sectional retrospective study conducted in Enugu, Nigeria which showed increased incidence of CNS anomalies in mothers>35 years of age. 4 Some other studies have also shown that a direct relationship exists between maternal age and incidence of congenital anomalies and showing that a higher incidence has been reported in elderly primiparous mothers and low incidence with age <20 years. 6,7 A higher delivery rate in younger women may have contributed to the higher incidence of the condition in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Maternal febrile illness in the first trimester, maternal age >35 years, use of herbal medications, exposure to drugs, lack of use of periconceptional folic acid supplementation were the possible risk factors for various CNS anomalies especially neural tube defects, a closely related condition to hydrocephalus and these factors may impact the incidence of at least the congenital variety of hydrocephalus in any geographic area. 4 The epidemiological characteristics of hydrocephalus are not well explored and understood. Although several previous epidemiological, clinical, and experimental studies assessing various individual risk factors for CH have been conducted, given the high complexity of this entity and its several potential aetiologies, a complex multifactorial (genetic and environmental) aetiology may be responsible for any or all subtypes of hydrocephalus.…”
mentioning
confidence: 99%